Per-arnt-sim (PAS) domain kinase (PASK) as a regulator of glucagon secretion. - MacDonald, P; Rorsman, P (2011)
The physiological and pathophysiological regulation of glucagon secretion from pancreatic alpha cells remains a hotly debated topic. The mechanism(s) contributing to the glucose sensitivity of glucagon release and its impaired regulation in diabetes remain unclear. A paper in the current issue of Diabetologia by da Silva Xavier and colleagues (doi: 10.1007/s00125-010-2010-7 ) provides intriguing new insight into a metabolic sensing pathway mediated by the per-arnt-sim (PAS) domain kinase (PASK) that may contribute to both the paracrine and the intrinsic glucose regulation of alpha cells. Importantly, the authors show that PASK is decreased in islets from patients with type 2 diabetes, providing a potential mechanism for impaired suppression of glucagon by hyperglycaemia in this disease. Much work remains to be done to determine the exact role and mechanism of PASK in alpha and beta cells. Nevertheless, the present work introduces a new player in the metabolic regulation of glucagon secretion.